2020
DOI: 10.3390/agronomy10020171
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Agronomic Performance between Japonica/Indica Hybrid and Japonica Cultivars of Rice Based on Different Nitrogen Rates

Abstract: Previous studies have revealed that the japonica/indica hybrid rice has a higher yield potential, biomass production, and nitrogen (N) accumulation than japonica rice in China, however, at a single N application rate. It remains unclear whether it also occurs at a higher or lower N application rate under the same field condition. To investigate the effects of nitrogen application rates on grain yield, N uptake, dry matter accumulation, and agronomic N use efficiency, field experiments were conducted in Jinhua … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 36 publications
(58 reference statements)
2
7
0
Order By: Relevance
“…This results is not in agreement with [78], who found a significant increase in yield at 120 kg N ha −1 , and there was a decrease in yield due to an increase in nitrogen at 180 kg N ha −1 . Similar results have also been observed in previous studies [79][80][81], revealing that an excessive N application rate has no contribution to the achievement of high grain yield in rice.…”
Section: Effect Of Water Management Nitrogen Levels and Their Interaction On Yield Characteristics Of Ricesupporting
confidence: 91%
“…This results is not in agreement with [78], who found a significant increase in yield at 120 kg N ha −1 , and there was a decrease in yield due to an increase in nitrogen at 180 kg N ha −1 . Similar results have also been observed in previous studies [79][80][81], revealing that an excessive N application rate has no contribution to the achievement of high grain yield in rice.…”
Section: Effect Of Water Management Nitrogen Levels and Their Interaction On Yield Characteristics Of Ricesupporting
confidence: 91%
“…Yield increased with increase in nitrogen level but any further increase in fertilizer amount to 150 kg N ha -1 showed no significant effects on yield, thus the yield followed this order 120>60>90>150>0>ABC .This is in agreement with Sah et al, 2019 who found significant increase yield at 120 kg N ha -1 , and there was decrease in yield due to increase in nitrogen at 180 kg N ha -1 . Similar results have also been observed in previous studies Sun et al, 2020: Hou et al, 2019Zhu et al, 2017 revealing that an excessive N application rate has no contribution to the achievement of high grain yield.…”
Section: Grains Yieldsupporting
confidence: 91%
“…In our study, the GY reached a peak at the N 140 level irrespective of all varieties; at the N 210 level, it was decreased. Many of the earlier investigations also revealed that the higher GY values of rice are not influenced by an excessive N application rate [72][73][74]. The risk of lodging was shown to increase due to the overuse of N fertilizers, which might significantly reduce the GY [75].…”
Section: Discussionmentioning
confidence: 99%